Исследование изменения физико-химических свойств водопроводной воды под воздействием мощных подводных искровых разрядов - Винников, Д.В.; Корытченко, К.В.; Ткачев, В.И; Егоренков, В.В.; Кудин, Д.В; Мирная, Т.Ю. (Електротехніка і електромеханіка, 2017)
Представлены результаты экспериментального исследования изменения физико-химических свойств водопроводной
воды под воздействием мощных подводных искровых разрядов атмосферного давления. Выявлена зависимость изменения окислительно-восстановительного потенциала и рН обрабатываемой воды от параметров импульсов, задаваемых параметрами электрической разрядной цепи, и их количеством. Исследования проведены на разрядных электродах, изготовленных из материалов двух типов: нержавеющая сталь и графит. Надані результати експериментального дослідження змінення фізико-хімічних властивостей водопровідної води під
впливом потужних підводних іскрових розрядів атмосферного тиску. Виявлена залежність змінення окисновідновлювального потенціалу і рН оброблюваної води від параметрів імпульсів, що задаються параметрами електричного розрядного кола, та їх кількістю. Дослідження проведені на розрядних електродах, виготовлених з матеріалів
двох типів: нержавіюча сталь і графіт. Purpose. The purpose of this investigation is to study the
changes in the redox potential and pH-value of the tap water
as a function of underwater spark discharges, storage device
capacitance and the charging voltage. Methodology. To define
the electric parameters of discharge circuit we used the
Rogowski loop and the compensated capacitance-ohm potential divider. To determine water properties before and after
the treatment we used the following devices: the water analyzer Anion -7051 with the limit of absolute error of the EMF
measurement ± 2 mV, the BANTE 902 device with the absolute
error of ± 0.002 рН. Results. We managed to establish the
time of the origination of changes in the properties of treated
water. A change in the positive redox potential to a negative
one occurred already after the third pulse at a total energy
input of ≥ 1 kJ. The pH value increased in the range of 0.2 –
0.45 рН units. We obtained the relationship of a change in the
redox potential as a function of total energy of the pulse train
that actually exhibits the linear relation to the mass of erosion
products. We established that the electrodes made of stainless
steel and the electrodes made of graphite provide similar
changes in water properties. An increase in pH is indicative of
the progress of reactions that result in the formation of ОН⎯.
Originality. The obtained experimental data prove a rapid and
reliable change in the redox potential from positive to negative
changes in the redox potential exponent can persist during ten
days and even longer. The erosion products of electrodes can
be removed from the treated water using the method of magnetic separation. Practical value. The «HYDRA» plant can be
used as the electrochemical ideal mixing reactor of a discrete
action with the removal of erosion products of the electrode
using the method of magnetic separation.